Convalescent Plasma for Hospitalized COVID-19 Patients: A Single-Center Experience - Massimo Franchini; Claudia Glingani; Giuseppe De Donno; Giuseppe Lucchini; Massimiliano Beccaria; Massimo Amato; Gian Paolo Castelli; Leonardo Bianciardi; Mauro Pagani; Marco Ghirardini; Giuseppe Puma; Barbara Presciuttini; et al. (Life, 2022)
In Winter 2020, Italy, and in particular the Lombardy region, was the first country in the Western hemisphere to be hit by the COVID-19 pandemic. Plasma from individuals recovered from COVID-19 (COVID-19 convalescent plasma, CCP) was the first therapeutic tool adopted to counteract the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). In this retrospective cohort study, we report the experience of the city hospital of Mantua, Lombardy region, on the compassionate use of CCP in patients hospitalized for severe COVID-19. Between April 2020 and April 2021, 405 consecutive COVID-19 patients received 657 CCP units with a median anti-SARS-CoV-2 neutralizing antibody (nAb) titer of 160 (interquartile range (IQR), 80–320). Their median age was 68 years (IQR, 56–78 years), and 62% were males. At enrollment, 55% of patients had an increased body mass index (BMI), and 25.6% had at least three comorbidities. The 28-day crude mortality rate was 12.6% (51/405). Young age (<68 years), mild disease (admission to low-intensity departments) and early treatment (<7 days from symptoms onset) with high nAb titer (≥320) CCP were found as independently associated with a favorable response to CCP treatment. No safety concerns were recorded, with a rate of CCP-related adverse reactions (all of mild intensity) of 1.3%. In our real-life experience, the first in the western world, early administration of high-titer CCP was a safe and effective treatment for hospitalized COVID-19 patients.